Abstract 15 Safety of DUOC-01, Intrathecal Cord Blood-Derived Cellular Therapy, as an Adjunct to Allogeneic Cord Blood Transplantation in Children with Inherited Metabolic Diseases. (6th September 2022) - Sun, Jessica; Baker, Jennifer; Cheatham, Lynn; Millette, Drew; Prasad, Vinod; Kurtzberg, Joanne
Abstract: Introduction: Unrelated donor umbilical cord blood transplantation (CBT) improves function and extends life in children with certain inherited metabolic diseases (IMDs); however, progressive neurologic decline often occurs during the few months post-CBT prior to donor engraftment in the brain, causing residual, irreversible impairments. We previously described donor engraftment in the brain after CBT and developed DUOC-01, a monocyte-derived CB cell product, to attempt to accelerate donor cell delivery to the brain. Objective: The objective of this study was to determine manufacturing feasibility and safety of intrathecal DUOC-01 in a phase I study in children with IMDs undergoing CBT after myeloablative cytoreduction (busulfan/cyclophosphamide/anti-thymocyte globulin). Methods: DUOC-01 was manufactured in adherent cell culture in a GMP lab over 21 days with a target dose of ≤100 × 10 5 cells. When cell dose permitted, 80% of the CB unit was used for transplant and 20% of the same unit was used to manufacture DUOC-01. Otherwise, DUOC-01 was manufactured from a unique CB unit. On day ≥+28 post-CBT, if there was evidence of hematopoietic engraftment without severe graft versus host disease or morbidity, DUOC-01 cells were harvested and administered intrathecally. Safety was monitored via neurologic exams, neuroimaging, and CSF studies. Results: Forty patients (aged 0-15 years) underwent CBT, 37 engrafted with donor cells. Median infused total nucleated cell count was 6.5 × 10 7 /kg (range 2.9-33.1 × 10 7 /kg); median time to neutrophil engraftment was 20 days (range 13-46 days). Ten patients did not receive DUOC-01 cells for the following reasons: engraftment failure (3), transplant-related morbidity (4), and low manufacturing yield (3). Thirty patients received 0.2-100 × 10 5 DUOC-01 cells intrathecally for a median of 31 days (range 27-77 days) post-CBT (19 with the same CB donor and 11 with a unique CB donor). Two patients developed transient fever and hypotension hours after unique-donor DUOC-01, consistent with an inflammatory response. Hydrocortisone (HC) was added to the final formulation, and post-validation, seven additional patients received unique-donor DUOC-01+HC without incident. No other DUOC-01-related serious adverse events occurred. Discussion: DUOC-01 is a CB-derived product intended to accelerate donor cell delivery to the brain of children with IMDs undergoing CBT. Intrathecal DUOC-01 administration is well-tolerated post-CBT from the same donor and, with the addition of HC, also from a unique donor. Escalating DUOC doses are being tested for safety and exploration of potential efficacy in a phase Ia trial of adults with multiple sclerosis.